Deteksi Jenis Penyakit melalui Perubahan Warna Kuku dengan Teknik Image Processing - Emil Herdiana; Lia Saniah; Fitriani Reyta (Ma'soem University, 2022)
Health is an important thing that is needed in order to maintain endurance, in the modern era types of diseases continue to grow very rapidly, these changes can be caused by several factors, these factors can be from food and lifestyle. , we can't deny the lifestyle in the modern era causes a person to forget to take care of their health, this is because the activities and activities are very dense, sometimes without realizing it makes the body's resistance to a disease less so that our body is susceptible to disease. viruses and diseases, this type of disease can attack and damage internal and external organs. Naturally, the body will respond to changes, these changes can show symptoms of an attack, diseases can be categorized from mild to high levels, for example, people who experience hair loss who continue to show cancer, either early or advanced cancer, another example is nail discoloration, for example. one yellow nail indicates the person has jaundice, another indication the nail has a long black line, this indication can be recognized. as a digestive problem in our body. For those who are experts, they will have experience in recognizing diseases and their indications, solutions will soon be found by buying preventive medicine, or other methods by directly consulting a doctor. The problem faced today is that a person is sometimes unconscious and does not observe changes in the body and even considers these changes to be normal, even though the body is trying to provide a natural warning system for the appearance of a disease symptom. image-processing based application, this application is used to identify changes in nail color and texture, these changes will be identified and processed using an image processing algorithm, this algorithm has a high accuracy value, the application will read nail color changes and identify and diagnose symptoms of disease in our body, the identification results have an accuracy of up to 85%.